Optical investigations of GaInNAs/GaAs multi-quantum wells with low nitrogen content - Sun, Handong (2009)
The optical properties of GaInNAs/GaAs multi-quantum wells were investigated by photoluminescence excitation (PLE) spectroscopy, as well as by photoluminescence (PL), under various excitation intensities and at various temperatures. The PLE spectra demonstrated pronounced excitonic features and the corresponding transitions were identified. At low temperatures the PL spectra were sensitive to the excitation intensity. Under fixed excitation intensity, both the peak energy and the linewidth of photoluminescence showed anomalous temperature dependence, specifically an S-shaped temperature dependence of the peak energy and a N-shaped temperature dependence of linewidth in the PL spectra. The observed results are explained consistently in terms of the exciton localization effect due to the local fluctuations of nitrogen concentration.